1972
DOI: 10.1007/bf02628896
|View full text |Cite
|
Sign up to set email alerts
|

Influence of solvent on degree of acylation in the formation of sucrose esters

Abstract: Sucrose palmitates were prepared by the interesterification of sucrose and methyl palmitate in different solvents. The ratio of methyl palmitate to sucrose in dimethylformamide (DMF) solution was varied so that the effect on yield and ester composition could be evaluated. When sucrose esters were prepared in DMF, the palmitoyl groups approximated a random distribution when only penta-and lower esters were formed. When the proportion of palmitoyl groups was increased, hexa-through octaesters were formed, but th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1974
1974
1999
1999

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 5 publications
(3 reference statements)
0
6
0
Order By: Relevance
“…Typically, the sugar polyesters (SPE) are prepared through base-catalyzed transesterification of carbohydrates with fatty acid methyl esters, using sodium methoxide as catalyst [91][92][93][94][95] . However, some of these methods require very high temperatures (above 100 °C) and toxic low-volatile solvents (e.g.…”
Section: Fatty Acid Esters Of Carbohydratesmentioning
confidence: 99%
“…Typically, the sugar polyesters (SPE) are prepared through base-catalyzed transesterification of carbohydrates with fatty acid methyl esters, using sodium methoxide as catalyst [91][92][93][94][95] . However, some of these methods require very high temperatures (above 100 °C) and toxic low-volatile solvents (e.g.…”
Section: Fatty Acid Esters Of Carbohydratesmentioning
confidence: 99%
“…Infrared and C-13 NMR results illustrated that raffinose polyesters were synthesized by sodium metal catalyzed interesterfication of raffinose undecaacetate and FAME of long chain fatty acids. Analyses of sucrose polyesters by NMR (Mima and Kitamori, 1964) and TLC (Weiss et al, 1971(Weiss et al, , 1972Rizzi and Taylor, 1978;Mieth et al, 1983;Hamm, 1984) have been reported. Figure 6 illustrates a proposed general reaction pathway for raffinose polyester synthesis.…”
Section: Figures 2 and 3 Illustrate Tlc Analyses Of Synthesized Rpementioning
confidence: 99%
“…1976Jandacek and Webb, 1978;Mieth et al, 1983). Sucrose polyesters can be prepared by interesterification, but frequently high temperatures and toxic solvents, such as dimethylacetamide, dimethylformamide, or dimethylsulfoxide, are required (Mattson et al, 1971;Weiss et al, 1971Weiss et al, , 1972Bobalek, 1977), and the sucrose polyesters are, therefore, not suitable for food applications.Authors Akoh and Swanson are affiliated with the…”
mentioning
confidence: 99%
“…This process was commercialized in 1960 by Dai-Nippon Sugar Manufacturing Co. Ltd. of Japan for use in the food industry (13). Other applications in drying oil production for varnishes, paints, and other finishes have been explored and patented (14), using a variety of slightly modified synthesis methods (15)(16)(17)(18)(19)(20). The use of isomeric xylenes as solvents to replace DMF was studied by Curtis in 1961 (21).…”
Section: Sucrose Estersmentioning
confidence: 99%